2022
DOI: 10.1002/wcc.772
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of climate change impact models

Abstract: In-depth understanding of the potential implications of climate change is required to guide decision-and policy-makers when developing adaptation strategies and designing infrastructure suitable for future conditions. Impact models that translate potential future climate conditions into variables of interest are needed to create the causal connection between a changing climate and its impact for different sectors. Recent surveys suggest that the primary strategy for validating such models (and hence for justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…In practice, the quantification of risk with climate-risk models is particularly challenging as it involves dealing with the absence of robust verification data (Matott et al, 2009;Wagener et al, 2022) when setting up the hazard, exposure, and vulnerability sub-models, as well as dealing with large uncertainties in the input parameters and the model structure itself (Knüsel, 2020). For example, in hazard modelling, many authors have shown large uncertainties affecting the computation of flood maps through hydraulic modelling (Merwade et al, 2008;Dottori et al, 2013); similarly, alternative models have been proposed for modelling tracks and intensities of tropical cyclones (Emanuel, 2017;Bloemendaal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the quantification of risk with climate-risk models is particularly challenging as it involves dealing with the absence of robust verification data (Matott et al, 2009;Wagener et al, 2022) when setting up the hazard, exposure, and vulnerability sub-models, as well as dealing with large uncertainties in the input parameters and the model structure itself (Knüsel, 2020). For example, in hazard modelling, many authors have shown large uncertainties affecting the computation of flood maps through hydraulic modelling (Merwade et al, 2008;Dottori et al, 2013); similarly, alternative models have been proposed for modelling tracks and intensities of tropical cyclones (Emanuel, 2017;Bloemendaal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Existing metrics such as the expected value of information and the value of the stochastic solution typically assume the availability of a stochastic model (Birge 1982, Bistline 2015. There are sensitivity frameworks based on deterministic model runs to guide decision-makers, analysts, and other stakeholders on whether more sophisticated methods are appropriate and to prioritize information gathering on uncertain factors (Herman et al 2015, Pianosi et al 2016, Quinn et al 2019, Wagener et al 2022. However, these approaches have largely been neglected in energy systems context in favor of stochastic optimization approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Surrogate models are learnt in order to replace a complicated model with an inexpensive and fast approximation. Parameters reduction is achieved based on either principal component analysis or global sensitivity analysis to determine which parameters significantly impact model outputs and are essential to the 160 analysis (Degen et al, 2022;Wagener, Reinecke, and Pianosi, 2022). Remarkably, versions of the model learning option do not need any prior information about model equations Eɱ but require local verification of conservation laws in the data ɗ (Lu and Lermusiaux, 2021).…”
mentioning
confidence: 99%
“…O1. Credibility of predictions is judged in terms of physical consistency checks (Wagener, Reinecke, and Pianosi, 2022) and by examining the ability of models to reproduce disruptive changes recorded in the data (Alley, 2004). O2.…”
mentioning
confidence: 99%
See 1 more Smart Citation